IMPLEMENTASI PROJECT-BASED LEARNING TERINTEGRASI PENDEKATAN SAINTIFIK PADA PEMBELAJARAN DAPUR KOMPOS UNTUK MENINGKATKAN KETERLIBATAN DAN PEMAHAMAN KONSEPTUAL SISWA KELAS V SDN JATI PULO 01 PAGI - Lestari Lydia Sigalingging (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This classroom action research aims to enhance student engagement and conceptual understanding in organic waste management through the implementation of a Scientific Approach-Integrated Project-Based Learning model. Conducted over three sessions with 32 fifth-grade students at SDN Jati Pulo 01 Pagi, this study employed a composting project using Takakura composters as the main learning activity. Data collection encompassed observation, conceptual tests, and project assessment. Findings demonstrated substantial improvements in learning motivation, collaborative skills, and conceptual grasp of recycling principles. The primary achievement manifested in students' capacity to connect theoretical knowledge with practical implementation. The study concludes that the integrated PjBL model effectively creates meaningful learning experiences in environmental education. Recommended follow-up measures include establishing a continuous monitoring program and disseminating the model across school levels.